2013
DOI: 10.1007/s11064-013-1005-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Withania somnifera Root Extract in Maneb–Paraquat Induced Mouse Model of Parkinsonism

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder and these days a lot of emphasis is given on the treatment of this disease using herbal medicines. The present study evaluates the neuroprotective effect of Withania somnifera (Ws) root extract on Parkinsonian mice. The mice were divided into three groups; the first group served as control, the second group was given maneb (MB) and paraquat (PQ) and the last group was administered MB-PQ along with Ws root extract for 3, 6 and 9 weeks. The behavioral stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 46 publications
4
46
0
Order By: Relevance
“…Ashwagandha extracts also showed ameliorative effects against other neurodegenerative disease models such as Parkinson's disease and Huntington's disease, [55][56][57][58][59][60] suggesting that Ashwagandha may be useful against various neurodegenerative diseases (Table 1). Additionally, a novel drug candidate for spinal cord injury was synthesized as a derivative of constituents of Ashwagandha.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashwagandha extracts also showed ameliorative effects against other neurodegenerative disease models such as Parkinson's disease and Huntington's disease, [55][56][57][58][59][60] suggesting that Ashwagandha may be useful against various neurodegenerative diseases (Table 1). Additionally, a novel drug candidate for spinal cord injury was synthesized as a derivative of constituents of Ashwagandha.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies of Ashwagandha will probably contribute to resolving an urgent unmet medical need: efficacious treatments that may offer cure of neurodegenerative diseases. 17) Memory improvement 38) Neuroprotective effects in vitro 33,35) Aβ clearance in vivo 38) Withanolide A Neurite outgrowth in vitro 18,19) Axonal regeneration and synaptic reconstruction in vitro and in vivo 21) Memory improvement 21) Upregulation of BACE1, ADAM10 and IDE in vitro 31) Withanoside IV Neurite outgrowth in vitro 18,19) Axonal regeneration and synaptic reconstruction in vitro and in vivo 22) Memory improvement 22) Withanoside VI Neurite outgrowth in vitro 18,19) Axonal regeneration and synaptic reconstruction in vitro and in vivo 23) Memory improvement 23) Sominone Axonal regeneration and synaptic reconstruction in vitro 22) Axonal growth in vivo 28) Memory improvement 27) and memory enhancement 28) Denosomin Axonal regeneration and neuroprotective effect in vitro 45) Withanone Neuroprotective effects in vitro 35) Spinal cord injury Withanoside IV Axonal growth in vivo and functional recovery 43) Denosomin Axonal growth in vivo and functional recovery 45) Parkinson's disease Extract Anti-oxidant effect in vivo [55][56][57][58][59] Neuroprotective effect in vivo 55,59) Functional recovery [55][56][57][58][59] Huntington's disease Extract Anti-oxidant ef...…”
Section: Resultsmentioning
confidence: 99%
“…33 Reports indicate that paraquat crosses blood-brain barrier through the neutral amino acid transporter. 34 It is suggested that the pathological hallmarks of PD involving selective vulnerability of dopaminergic degeneration, a characteristic feature of paraquat neurotoxicity. 35 Studies have shown that paraquat-induced cell loss results from Bak-dependent pathway involving mitochondrial membrane permeabilization and subsequent activation of caspase-3.…”
Section: -4mentioning
confidence: 99%
“…Ws extract was found to reverse levels of reduced glutathione, GPX, SOD and CAT significantly in a dose-dependent manner as compared to 6-OHDA rat model [31]. Also Prakash J et al2013., [13] Girdhari LG and Avtar CR.2009., [36] worked on synergistic effect of Ws and L-dopa in the inhibition of haloperidolinduced catalepsy in mice. The anti-cataleptic effect of Ws could be attributed to polyphenols present in it responsible for direct scavenging of free radicals and also by inhibition of lipid peroxidation in the central nervous system.…”
Section: Scientific Work Done On Withania Somnifera For Treating Pd Ementioning
confidence: 99%
“…The dried roots of Ashwagandha are found to be useful in the treatment of nervous and sexual disorders [11,12]. The biological activity of Ws extract showed antioxidant and free radical scavenging potential [13]. Additionally, Ws is a potent neuronal tonic and has been expected to be used in the treatment of many neurological deficits including epilepsy [14], poor memory [15], depression [4] and PD [6] in animal model.…”
Section: Introductionmentioning
confidence: 99%